Ecological spirituality: a new way to get closer to god from the world - Pérez P, Victorino (Editorial Pontificia Universidad Javeriana, 2010)
From a positive assessment of environmentalism, in its biosocial dimension, it is imperative to explore an ecological spirituality in connection with biblical wisdom and the old religious traditions. This spirituality is based on three points: (1) An empathy connection with reality that overcomes anthropocentrism and goes further from “materiality” of matter to open itself to its spiritual dimension. (2) A way to conceive God and the relation with him, passing from the Lord’s ruling to the Gardener’s care, from the dominating God to the Trinitarian God, Father and companion, mother, lover, and friend. (3) To see the world from a cosmoteandricperspective.